1998
DOI: 10.1901/jaba.1998.31-339
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis and Treatment of Destructive Behavior Maintained by Termination of “Don't” (And Symmetrical “Do”) Requests

Abstract: We used descriptive assessment information to generate hypotheses regarding the function of destructive behavior for 2 individuals who displayed near‐zero rates of problem behavior during an experimental functional analysis using methods similar to Iwata, Dorsey, Slifer, Bauman, and Richman (1982/1994). The descriptive data suggested that destructive behavior occurred primarily when caregivers issued requests to the participants that interfered with ongoing high‐probability (and presumably highly preferred) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 42 publications
5
58
0
1
Order By: Relevance
“…For example, Murphy et al found that aggression increased substantially when the therapist blocked the participant from engaging in rituals (flushing papers, collecting and hiding household items). It is possible that problem behavior in this case may function to terminate blocking and gain (or regain) access to repetitive behaviors (i.e., a response-response relation; Fisher, Adelinis, Thompson, Worsdell, & Zarcone, 1998;Hagopian et al, 2007). One intervention that has proven to be effective when this response-response relation exists is functional communication training (FCT; Fisher et al).…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…For example, Murphy et al found that aggression increased substantially when the therapist blocked the participant from engaging in rituals (flushing papers, collecting and hiding household items). It is possible that problem behavior in this case may function to terminate blocking and gain (or regain) access to repetitive behaviors (i.e., a response-response relation; Fisher, Adelinis, Thompson, Worsdell, & Zarcone, 1998;Hagopian et al, 2007). One intervention that has proven to be effective when this response-response relation exists is functional communication training (FCT; Fisher et al).…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…However, the variables that we were interested in measuring were primarily influenced by developments in effective prompting and differential reinforcement strategies derived from the empirical literature on the treatment of noncompliance and escape-maintained problem behavior. From this literature, we identified the following strategies that appeared to be relevant to the treatment of compliance in classrooms: integral directive prompting (often referred to as three-step prompting; Horner & Keilitz, 1975;Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990), embedding prompts in preferred activities (Carr, Newsom, & Binkoff, 1980;, framing instructions as ''do'' commands as opposed to ''don't'' commands (Adelinis & Hagopian, 1999;Fisher, Adelinis, Thompson, Worsdell, & Zarcone, 1998;Neef, Shafer, Egel, Cataldo, & Parrish, 1983), eliminating escape from instructions by continuing prompting until the task is completed (also known as escape extinction; Iwata, Pace, Cowdery, & Miltenberger, 1994;Iwata et al, 1990;Zarcone et al, 1993), and providing social positive and negative reinforcers for compliance (Lalli et al, 1999;Parrish, Cataldo, Kolko, Neef, & Egel, 1986;.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Functional analyses consisted of an alone or an ignore condition (specific to each participant), attention, demand, tangible, and toy play conditions. In addition, analyses included a ''do'' requests condition for Brent (similar to that described by Fisher, Adelinis, Thompson, Worsdell, & Zarcone, 1998) and a modified tangible condition for Jason. During pairwise analyses for Brent and Jason, test conditions were compared to control conditions via sequential presentations .…”
Section: Phase 1: Functional Analysis Proceduresmentioning
confidence: 99%